Estimating the Uplift Bearing Capacity of Belled Piers Adjacent to Sloping Ground by Numerical Modeling Based on Field Tests - Yangchun Han; Jiulong Cheng; Weifeng Zheng; Shijun Ding (Advances in Civil Engineering)
In order to evaluate the uplift bearing capacity of belled piers beside slopes, a series of numerical simulations are carried out based on field tests data. First, a number of uplift loading tests of full-scale belled piers are carried out on the project site of transmission line in Anhui Province, China. Second, a slope-foundation model for numerical modeling is proposed and calibrated based on field tests data. The behavior of belled piers adjacent to slopes subject to uplift load is studied by numerical modeling. The impact of three parameters, including distance (a) from the belled pier to the crest of the slope, slope angle (β), and embedment depth (h) of the belled pier, has been investigated on the uplift capacity of the belled pier. Based on the simulation results, an attenuation coefficient (ω) is put forward for evaluating the reduction of uplift bearing capacity of the belled pier. The results show that the coefficient ω is negatively correlated with distance a and depth h, and the influence of distance a is greater than that of depth h according to the results of variance analysis, but the difference is not significant by F test. Moreover, the empirical equation between attenuation coefficient ω and three key factors a, β, and h had been presented by a series of fitting.